Answer:
x = 6
y =-2
Step-by-step explanation:
We need to solve the following system of equaitions:
x - 2y = 10 [I]
3x + 2y = 14 [II]
First. We are going to solve the first equation for 'x':
x = 10 + 2y
Now, let's substitute the value of 'x' into the second equation:
3x + 2y = 14 → 3(10 + 2y) + 2y = 14
Simplify: 3(10 + 2y) + 2y = 14 → 30 +6y + 2y = 14 → 30 + 8y = 14
Solve for 'y': 30 + 8y = 14 → 8y = -16 → y =-2
Now that we know the value of 'y', let's find the value of 'x':
x - 2y = 10 → x - 2(-2) = 10 → x = 6